PENGARUH PAJAK TERHADAP TINGKAT KESEHATAN DAN PENDIDIKAN MASYARAKAT YOGYAKARTA - Saras Shinta Qurrota; Ghiyats Furqan Dewantara; Aditya Kumala Dewi (POLITEKNIK LP3I JAKARTA, 2025)
This study is aims to investigate the effect of personal income tax to improving the welfare in Yogyakarta. The level of health and level of education are used as a reference in measuring the level of welfare in Yogyakarta. The data in this study are in the form of realization of personal income tax data, health sector expenditure data and education sector expenditure data in the period 2008-2017 obtained from the realization report of personal income tax in the Directorate General of Taxes of DIY and the realization report of APBD at the Directorate General of Fiscal Balance. This research uses quantitative methods, while the data analysis technique used in this study is regression analysis. The results of this study indicate that there is an effect of the personal income tax on the level of education both at the provincial and regional levels or the city of Yogyakarta. For the effect of personal income tax on the level of health only occurs at the district or city level, while at the provincial level there is no effect between the personal income tax on the level of health.